2020
DOI: 10.3390/ijerph17061883
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Role of Interpersonal Communication, Traditional Media and Social Media in Pro-Environmental Behavior: A China-Based Study

Abstract: Previous studies have confirmed that information exposure affects pro-environmental behavior. With the rise of social media, new questions emerge in terms of whether different types of information exposure affect pro-environmental behavior differently. Based on a survey of 550 people that was carried out in China, this study aims to compare the different roles of interpersonal communication, traditional media, and social media in affecting the relationships between people’s environmental risk perception, willi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 56 publications
6
70
1
1
Order By: Relevance
“…The specific measurement content includes whether people obtain the four aspects of information through the above media. The specific measurement items refer to our other research [ 54 ]. One point is scored for each item.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific measurement content includes whether people obtain the four aspects of information through the above media. The specific measurement items refer to our other research [ 54 ]. One point is scored for each item.…”
Section: Methodsmentioning
confidence: 99%
“…The internal consistency coefficient of the scale composed of 12 items is 0.818, and the average and standard deviation are 3.74 and 0.93, respectively. For the measurement of the above control variables, please refer to our related research [ 54 ]. See Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Because of their popularity and entertainment value, television and internet can be used as a carrier of environmental risk and health-related information for migrant construction workers with low educational level. Environmental risk and health-related information can guide migrant construction workers’ healthy lifestyle, and improve their physical or mental health [ 91 , 92 ]. Therefore, in order to further improve migrant construction workers’ health and environmental welfare, the government should continue to provide television and internet network infrastructures, and provide guidance on internet usage to migrant construction workers.…”
Section: Discussionmentioning
confidence: 99%
“…Vyncke, Perko, and Van Gorp (2017) classified media into two categories: traditional and internet social . Compared with traditional media, internet social media is more mobile and interactive, and has become the main channel for the public to obtain news information and the government to carry out risk communication (Intravia et al 2017;Han and Xu 2020). The consumption of different media types may have different relationships with PRP.…”
Section: Media Typementioning
confidence: 99%
“…That is, media type may moderate the relationship between media consumption and PRP. First, in terms of the relationship between GMU and PRP, according to Han and Xu (2020), compared with traditional media, online social media is more interactive and diverse in information sources, and its use of people's environment risk perception has a significant amplification effect. Moreover, judging from the relationship between SMEX and PRP, a study conducted after the Fukushima nuclear accident in Japan revealed that exposure to the continuous reporting of nuclear accidents on traditional media (e.g.…”
Section: Media Typementioning
confidence: 99%